Outcomes of inpatient mobilization: a literature review - Kalisch, Beatrice J; Lee, Soohee; Dabney, Beverly W (Journal of clinical nursing, 2014)
Aims and objectives To review current research evidence on the outcomes of mobilising hospitalised adults. Background Although immobility is known to cause functional decline or complications, inpatient ambulation emerged as the most often missed element of nursing care. This study is designed to review research studies that give evidence as to the consequences of mobilising or not mobilising hospitalised adult patients. Design A literature review of published peer‐reviewed empirical research was undertaken. Methods The electronic databases of MEDLINE (Ovid), CINAHL, and PubMed were accessed to search for relevant empirical articles, supplemented by a search of reference lists contained in retrieved articles and citation tracking. Results Thirty‐six studies were identified for inclusion in the review. Four areas (study design, sample size, measurement and statistical analysis) were evaluated for methodological quality, and most studies showed strong quality. A synthesis of the findings generated four themes of the effects of inpatient mobilisation: (1) physical outcomes included pain, deep vein thrombosis, fatigue, etc.; (2) psychological outcomes included anxiety, depressive mood, distress, comfort and satisfaction; (3) social outcomes included quality of life and independence; and (4) organisational outcomes included length of stay, mortality and cost. Conclusion Mobilising hospitalised adults brings benefits for not only physical functioning, but also their emotional and social well‐being. Moreover, ambulation yields important organisational benefits. These benefits of mobilisation on four areas required viewing the patient in a holistic manner. Even though each study approached different types of patients, illnesses and procedures, this review showed that most inpatients would benefit from mobilisation and would experience optimal functions. Relevance to clinical practice The importance of mobilisation for positive patient outcomes highlights the need to develop methods to ensure that this nursing action is completed on a systematic basis.